Konflik Agraria dan Keterlibatan Rezim Lokal pada Konflik Desa Wadas - Salsabila, Ananda Syifa; Sefani, Ainur; Kirsanto, Talitha Nabila; Arsita, Lia Yuni; Nurdin, Nurdin (Jurnal Administrasi Pemerintahan Desa, 2024)
The agrarian conflict in Wadas Village, Purworejo Regency, is rooted in the planned construction of the Bener Dam, located in Purworejo Regency, Central Java. The role of the ruling regime at that time is crucial in addressing this agrarian conflict, considering the significant autonomy granted to local governments during the reform era. However, the efforts by the local government to resolve the conflict were unsuccessful, leading to prolonged agrarian tensions. The main objective of this research is to examine the involvement of the local regime in triggering the agrarian conflict in Wadas Village and their participation in conflict resolution efforts, as observed through Law No. 5 of 1960. The research methodology employed is qualitative, using literature review techniques to analyze journals, books, and news related to the study. The findings indicate the involvement of the local regime in sparking the agrarian conflict in Wadas Village and their diverse efforts to resolve the issues, despite facing challenges. Additionally, the government has implemented resolutions to assist in conflict resolution, although a mutually beneficial solution has not yet been found.